(3NGU HGdCcGOjejjf hGdegfjjf s - (3HGOjS(B, (3eLGfjs ((3GdLRGFQ(B:s (3efThQGJ CdaG ddhKGFb(B,s, 2018)
(3JfGhd gPG GdcJGH ehVhY GdcJGHI ddGPGYI hGdJdaRjhf, hJWQb HGdOQGSI Gdi eGgjI GdUMGaI ef fGMjI GdJMQjQ GdUMaj (B( (3GdJbQjQ, GdJYdjb, GdYehO, GdebGd(B) (3,h cjajI cJGHI GdNHQ GdUMaj hefg GdJZWjI GdUMajI hhcGdGJ GdCfHGA, HGdGVGaI Gdi GdeQGSd GdUMaj aj GdGPGYI hGdJdaRjhf hGdGTgGQ hGdHhQJQjg (B. s
(3GdHHdjhZQGajG U(B.205 s
Keywords: (3GdJMQjQ GdUMajs; (3GdJdaRjhfs; (3GdUMGaI(B: (3GdEPGYI hGdJdaRjhfs